Caracterización antropométrica en jugadores de elite de waterpolo - Vila, H.; Ferragut, C.; Abraldes, J. A.; Rodriguez, N.; Argudo, F. M. (Revista Internacional de Medicina y Ciencias de la Actividad Física y del Deporte, 2010)
The purpose of this study was designed to describe and to determine the anthropometric structure (i.e., body composition, anthropometric data) of the best Spanish water polo players competing in the junior and senior categories. Participants: Among the 20 participants (M= 24.07±14.96 years old), weight (M= 89.61±11.88kg, height (M= 186.91±6.91cm), and arm span (M= 195.95±9.10cm), 7 players and 13 players were competing in the junior and in the senior Spanish national team, respectively. Measures: Weight, height, arm span, four breadths and nine girths were measured in all players. Body fat percentage, muscle mass and the anthropometric data were calculated. A Student`s t-test was used to compare the two categories. Results: The anthropometrics factors, similar for both categories were not related to training level. Significant differences between categories were found in variables which kept indirect relation with physical strength and experience. The junior players presented a balanced mesomorph somatotype, while the senior players exhibited an endomorphic mesomorph somatotype